2013
DOI: 10.3390/antib2020270
|View full text |Cite
|
Sign up to set email alerts
|

Antibody-Directed Phototherapy (ADP)

Abstract: Photodynamic therapy (PDT) is a clinically-approved but rather under-exploited treatment modality for cancer and pre-cancerous superficial lesions. It utilises a cold laser or LED to activate a photochemical reaction between a light activated drug (photosensitiser-drug) and oxygen to generate cytotoxic oxygen species. These free radical species damage cellular components leading to cell death. Despite its benefits, the complexity, limited potency and side effects of PDT have led to poor general usage. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 159 publications
(177 reference statements)
1
29
0
Order By: Relevance
“…Several in vitro studies confirmed the interest of Ab-PS conjugates in PDT [226,227]. In most cases, a lower effective dose of Ab-PS conjugate was able to induce a higher selective phototoxic effect compared to PS or Ab alone.…”
Section: Monoclonal Antibodiesmentioning
confidence: 72%
See 1 more Smart Citation
“…Several in vitro studies confirmed the interest of Ab-PS conjugates in PDT [226,227]. In most cases, a lower effective dose of Ab-PS conjugate was able to induce a higher selective phototoxic effect compared to PS or Ab alone.…”
Section: Monoclonal Antibodiesmentioning
confidence: 72%
“…21.B) [227]. Antibody-based photosensitizer delivery may offer significant benefits over conventional PDT.…”
Section: Monoclonal Antibodiesmentioning
confidence: 99%
“…BL22 (anti-CD22 disulphide-linked Fv-Psuedomonas exotoxin), which is in advanced clinical trials for hairy cell leukaemia [93]. Such ScFv based carriers have shown more promise as vehicles for photosensitsiers, which are light-activated drug payloads [94]. Deonarain and co-workers demonstrated tumour cures using an anti-HER2 scFv optimised for PDT conjugation in collaboration with Photobiotics [95], whereas Boyle and co-workers focussed on a lower payload loading using the higher affinity antibodies as described by the Neri group [96].…”
Section: Antibody Fragments -Quick and Nimble Adcs? 341 Fab And Sinmentioning
confidence: 98%
“…Some of the advantages seen in PIT, compared to conventional cancer treatment such as chemotherapy/chemo-immunotherapy, is that during laser activation of the Ab-PS conjugate there is cell specific cytotoxicity of cancerous cells sparing the surrounding healthy tissue. Additionally PIT is neither immunosuppressive nor does it have an affinity for rapidly dividing cells, making it less likely to develop treatment induced resistance due to neoplastic cells up regulating alternative or circumventive pathways commonly seen in chemotherapy [48].…”
Section: Pdt and Lung Cancermentioning
confidence: 99%